An integrated approach based on phytochemistry, network pharmacology and metabolomics reveals the mechanism of action of Xanthium strumarium L. for allergic rhinitis. Issue 67 (11th November 2020) - Yao, Tie; Yan, Jiankun; Li, Yang; Wang, Jiaxin; Qiao, Miao; Hu, Xintong; Shi, Xuliu; Cao, Shijie; Qiu, Feng
Abstract : This study investigated the mechanism of Xanthium strumarium L. for allergic rhinitis through an integrated approach of phytochemistry, network pharmacology and metabolomics. Abstract : Xanthium strumarium L. (XS) is a traditional Chinese medicine (TCM) that has been widely used in Chinese medicine prescription for allergic rhinitis (AR). However, the action mechanisms of XS on the therapeutic effects on AR remain elusive. Herein, an integrated approach of phytochemistry, network pharmacology and metabolomics was first applied to uncover the action mechanisms of XS for AR. The therapeutic effect of XS extract on AR was evaluated in rat models of ovalbumin (OVA)-induced AR. The cytokine levels in rat serum and histopathological changes of nasal mucosa were assessed after oral treatment with XS. Chemical compositions of XS were elucidated by phytochemical methods, and active ingredients were identified via ADME-TOX screening in silico . Network pharmacology was performed to establish and analyze the compound-target-disease network so as to find the possible mechanism of XS in treating AR. In addition, metabolomics analysis was applied to investigate the changes in the endogenous metabolite levels that result from XS treatments. As result, the XS extract significantly increased the serum concentrations of IL-2 and reduced the levels of serum IL-4, while XS could ameliorate inflammation in the nasal sub-mucosal area, indicating that XS has significant therapeutic effects on AR model rats. Furthermore, a total of 119 compounds were isolated from XS, and 59 of these compounds were identified as active ingredients through ADME-TOX screening in silico . An in-depth analysis of the network pharmacology implied that the active ingredients of XS could regulate the inflammatory response via "multi-component, multi-target" patterns. In combination with the results of metabolomics, we found that the active ingredients of XS have a beneficial effect on AR through regulating the metabolism of arachidonic acid, which was reflected by medicating the Fc epsilon RI signaling pathway, and the neuroactive ligand–receptor interaction pathway, as well as the key proteins in arachidonic acid metabolism, such as PTGS2, PTGS1, PTGES and ALOX5. Additionally, molecular docking showed that multiple compounds have better binding with PTGS2 and ALOX5, which might be two crucial targets. Overall, these results suggest that the treatment of XS for AR is realized by regulating the metabolism of arachidonic acid via a combination form. This study provides the basis for clinical applications of XS.